A Review of the T-Stub Components for the Analysis of Bolted Moment Joints - Giovani Jesus Berrospi Aquino; Ana María Gómez Amador; Jorge Hernan Alencastre Miranda; Juan José Jiménez de Cisneros Fonfría (Applied Sciences, 2021)
The analytical method for the calculation of the properties of a bolted joint established by the structural Eurocodes proposes the T-stub as a component for the characterization of the tension and compression zones in moment joints. In this article, a review of the state of the art on the T-stub component is developed, where the works developed since it was initially defined, and from the perspectives of formulation, experimentation and numerical simulation are summarized and discussed. Additionally, possible future lines of work are proposed.